The Role of Social Capital in Risk Mitigation and Recovery Strategies in Supply Chains - A Systematic Literature Review - Birigeni, Zifegha C. (Cranfield University, 2025)
Abstract Global supply chains are increasingly exposed to a wide range of disruptions, from natural disasters and pandemics to geopolitical conflicts and technological breakdowns. Against this backdrop, resilience has emerged as a central concern for both scholars and practitioners. This thesis investigates the role of social capital in risk mitigation and recovery strategies in supply chains, focusing on how its structural, relational, and cognitive dimensions contribute to resilience. A systematic literature review (SLR) was conducted, analysing sixty peer-reviewed articles published between 2010 and 2025, drawn from Scopus and EBSCO databases. The thematic synthesis identified five interrelated mechanisms; trust, knowledge sharing, collaboration, flexibility, and shared norms, that explain how social capital operates as a systemic resource for resilience. The findings demonstrate that relational trust accelerates joint responses, structural capital enhances information flows and flexibility, and cognitive alignment through shared norms embeds a risk-aware culture that sustains long-term resilience. Together, these mechanisms highlight the interdependence of social and organisational ties in shaping risk mitigation and recovery capabilities. This research adds to theoretical debates and provides practical insights into an integrative framework of social capital and resilience, and to practice by offering actionable guidance for managers on cultivating trust, collaborative capacity, and cultural alignment in their networks. Limitations are acknowledged in terms of dataset scope and sectoral focus, but this research also identifies avenues for future research, including digital trust, informal networks, and cross-cultural perspectives. In summary, the thesis demonstrates that resilience is not solely a technical or structural capability, but a collective achievement rooted in the networks.
Keywords: Resilience; Collaboration; Knowledge sharing; Flexibility; Humanitarian logistics; Digitalisation